Lipoid proteinosis - Wollina, Uwe (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2004)
The case of a 37-year-old woman with lipoid proteinosis is presented. The first symptoms of hoarseness of voice occurred in puberty. Additional symptomsincluded beaded eyelid papules, macroglossia with yellowish papules, yellowish deposits of soft palate, popular eruption in the axillary area and tuberous nodules on the elbows.
Keywords: Adult; dermatologija; Diagnosis; Eyelid Diseases; Hialin; Hoarseness; Hripavost; Hyalin; Kožne bolezni; Lipoidna proteinoza; Lipoidproteinosis; Odrasli; Oral Manifestations; Skin Diseases; Ustne manifestacije; Veka, bolezni